Different Pollinators’ Functional Traits Can Explain Pollen Load in Two Solitary Oil-Collecting Bees - Maureen Murúa (Insects, 2020)
Functional traits have been shown to be a good predictor of pollen load for some pollinator bee species, but little is known about solitary bees. In this study, I used two solitary oil-collecting bees to explore the impact of functional traits on the pollen load of two oil-secreting Calceolaria species. I therefore measured the visitation frequency, the time spent manipulating the flower, pollinator body size and pollen load for each bee species. The results reveal that each pollinator visits different Calceolaria species (C. cavanillesii and C. filicaulis) for pollen and/or oil and at least another four herb species for pollen in different proportions. In addition, each bee species presents different functional traits that affect Calceolaria pollen load. For C. chilensis, it was only its body size that affected the Calceolaria pollen load, while in C. subcaeruleus, both body size and handling time together account for its pollen load. Overall, these results highlight the role of pollinators’ functional traits in different stages of the pollination process, and even more in specialized plant-pollination systems.